Smoking Related Questionnaire Scores Before and After Education Using Video and Leaflet among Adolescents - Yuyun Tuasikal (Innovative Approaches in Health Science Journal, 2026)
Background: Adolescent smoking remains a public health concern in Indonesia, while evidence on community-based smoking education in eastern Indonesia is limited. Video and leaflet materials offer practical approaches for delivering standardized tobacco-related information, but changes in immediate educational outcomes should be distinguished from changes in smoking behavior. Objective: To compare smoking-related questionnaire scores before and after video- and leaflet-based education among adolescents in the Laimu Public Health Center working area, Maluku, Indonesia. Methods: A one-group pretest-posttest study was conducted among 88 adolescents aged 10–18 years. Participants received smoking-related education using video and leaflet materials and completed the same questionnaire before and immediately after the educational session. Pretest and posttest scores were compared using the Wilcoxon signed-rank test. Results: Before the intervention, 38 participants (43.0%) were classified in the higher-score category (>25), compared with 77 (87.5%) immediately after the intervention. Individual paired comparisons showed higher posttest scores in 83 participants, a lower score in one participant, and unchanged scores in four participants. Posttest scores were significantly higher than pretest scores (Z = −7.963, p < 0.001). Conclusion: Smoking-related questionnaire scores increased immediately after video- and leaflet-based education among adolescents in the Laimu Public Health Center working area. The findings indicate a short-term improvement in the questionnaire outcome but do not establish smoking cessation or sustained behavioral change. Controlled studies with longer follow-up and behavioral outcomes are needed to determine whether these immediate changes persist and translate into changes in smoking behavior.